Range Cattle Research and Education Center Climatological Report — 2007 - Brent Sellers (EDIS)
SS-AGR-231, a 7-page illustrated research report by Brent Sellers, presents a summary of rainfall, air temperature, evapotranspiration, and solar radiation for 2007 obtained at the Range Cattle Research and Education Center (REC) in Ona, Florida, and is compared to a 66-year summary of data collected from this location. Published by the UF Department of Agronomy, September 2009.